Perubahan Fonetik pada Kata Serapan Bahasa Arab ke dalam Bahasa Jawa dalam Bahasa Harian - Kunhaniah Mabruroh (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2017)
The data that have been taken by the researchers in this study is the phonetic changes of Arabic word absorption in the Java language. While the object in this study is general, that is all the words that are prevalent in everyday life. While data collection techniques that have been used in this research is the technique of reading and writing. Reading activity is done to get the data deserve to be made in research material. When already get data that has been eligible for the check in through the Baoesastra Java Javanese dictionary and check also with the Arabic-language dictionary that is Al-Munir. Data analysis using the method of matching, namely by connecting lingual elements that are found in Arabic and Java language. While the results obtained are, show that the Arabic absorption word is not only absorbed into the Java language, but experienced some changes in categories, and changes in meaning. These changes involve branches of etymology, phonology, morphology, and semantics. Formal changes that occur through phonological and morphological adjustments. The shape changes that occur are un-ending changes, syllabic pattern adjustments, multiple plural changes, and phoneme adjustments. Phoneme changes occur because Arabic and Javanese languages have different phonemes.The phoneme changes include: 1. Change of vowel phoneme, 2. Long vocal changes into short vocals, 3. Changes diphthong into monophthong, 4. Vowel changes, 5. Consonant phoneme changes, 6. Duplicate consonant changes into a single consonant. Keywords: Phonetic Changes, Arabic Absorption Word into Javanese